Handbook of Popular Culture and Biomedicine Knowledge in the Life Sciences as Cultural Artefact - Görgen, Arno; Nunez, German Alfonso; Fangerau, Heiner (Springer International Publishing : Imprint: Springer, 2019)
This handbook explores the ways biomedicine and pop culture interact while simultaneously introducing the reader with the tools and ideas behind this new field of enquiry. From comic books to health professionals, from the arts to genetics, from sci-fi to medical education, from TV series to ethics, it offers different entry points to an exciting and central aspect of contemporary culture: how and what we learn about (and from) scientific knowledge and its representation in pop culture. Divided into three sections the handbook surveys the basics, the micro-, and the macroaspects of this interaction between specialized knowledge and cultural production: After the introduction of basic concepts of and approaches to the topic from a variety of disciplines, the respective theories and methods are applied in specific case studies. The final section is concerned with larger social and historical trends of the use of biomedical knowledge in popular culture. Presenting over twenty-five original articles from international scholars with different disciplinary backgrounds, this handbook introduces the topic of pop culture and biomedicine to both new and mature researchers alike. The articles, all complete with a rich source of further references, are aimed at being a sincere entry point to researchers and academic educators interested in this somewhat unexplored field of culture and biomedicine.